Effects of Part- and Whole-Object Primes on Early MEG Responses to Mooney Faces and Houses - Steinberg Lowe, Mara; Lewis, Gwyneth A.; Poeppel, David (Frontiers in Psychology, 2016)
Results from neurophysiological experiments suggest that face recognition engages a sensitive mechanism that is reflected in increased amplitude and decreased latency of the MEG M170 response compared to non-face visual targets. Furthermore, whereas recognition of objects (e.g., houses) has been argued to be based on individual features (e.g., door, window), face recognition may depend more on holistic information. Here we analyzed priming effects of component and holistic primes on 20 participants’ early MEG responses to two-tone (Mooney) images to determine whether face recognition in this context engages ‘featural’ or ‘configural’ processing. Although visually underspecified, the Mooney images in this study elicited M170 responses that replicate the typical face versus house effect. However, we found a distinction between holistic versus component primes that modulated this effect dependent upon compatibility (match) between the prime and target. The facilitatory effect of holistic faces and houses for Mooney faces and houses, respectively, suggests that both Mooney face and house recognition – both low spatial frequency stimuli - are based on holistic information.